Quantification of past sedimentary flux at continental scale: the case-study of Africa au Meso-Cenozoic times. - (:unkn) unknown (My University, 2009)
Deformation and climate are two known factors controlling relief erosion and the terrigeneous sedimentary flux preserved in downstream basins. In order to discuss the relative influence of both factors, we developed a method based on the integration of seismic lines from litterature in a 3D-model to quantify the volume preserved in passive margins, at a few Myr resolution, at continental scale, and over long periods of time (x 100 Myr). We also estimated errors associated with these quantifications. We applied this method along the West- African margin and corrected the results from the carbonate/ evaporite contribution to reach a terrigeneous volume. We obtained the evolution of terrigeneous sedimentary rate, showing that the deformation is the most important sedimentation accumulation trigger i) during rifting when rift shoulders are eroded and ii) during post-rift evolution when the continental domain is uplifted. Climate seems to highlight the uplift effect by runoff augmentation.
Keywords: African Research